Growing up American : how Vietnamese children adapt to life in the United States - Zhou, Min, 1956-; Bankston, Carl L. (Carl Leon), 1952- (Russell Sage Foundation, 1998)
"Growing Up American tells the story of Vietnamese children and sheds light on why their often troubled passage into American society has thus far been successful." "Drawing on research and insights from the U.S. census, survey data, and their own participant observation and in-depth interviews, Min Zhou and Carl Bankston focus on the Versailles Village enclave in New Orleans, one of many newly established Vietnamese communities in the United States, to examine the complex skein of family, community, and school influences that shape these children's lives. With no ties to existing ethnic communities, Vietnamese refugees had little control over where they were settled and no economic or social networks to offer them assistance. Growing Up American describes the process of building communities that were distinctive outgrowths of the new environment in which the Vietnamese found themselves. Familial and cultural organizations reformed in new ways, blending economic necessity with cultural tradition. These reconstructed social structures create a particular form of social capital that helps disadvantaged families overcome the problems associated with poverty and ghettoization."--Jacket